The stoic cosmos: conflagration, cosmogony, and recurrence in early stoicism - Salles, Ricardo (Cambridge University Press, 2025)
"A detailed and accessible reconstruction of the Stoic philosophical doctrine that our cosmos is periodically destroyed and restored. Explains its uniqueness compared to earlier cosmologies and refers to central questions in the interpretation of Stoicism, such as the role of the Stoic god in cosmology"